Wizerunek kobiety w polskich afektonimach w świetle teorii stereotypów płciowych - Jedziniak , Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
This article aims to present the image of a woman in Polish affectionate names in the light of the theory of gender stereotypes. Special attention has been paid to the linguistic and cultural status of female affectionate names. Based on the analysis of selected female affectionate names, the author demonstrates that they contain some women’s representations that depend on features assigned to women in social and cultural stereotypes (physical, mental and behavioural) such as beauty, grace, timidity, kindness, peace, protectiveness, modesty, etc. It has been noticed that this image can be both positive and negative.